An evaluation of the effect of different veneer materials on fracture resistance of zirconia core - Ibraheem, Yousra Abdulkareem; Alwahab, Zahraa Nazar (Brazilian Dental Science, 2021)
Objective: this in vitro study was done to evaluate the effect of packable P60 composite and Tetric N-Ceram composite veneer material on fracture strength of zirconia cores. Material and Methods: Twenty four zirconium cores (Vita, Germany) with 0.7 mm thickness were fabricated by CAD/CAM technology and then subjected to air abrasion with 50µm of Al2O3. Cores were randomly divided into three groups according to veneering material (group A: control group sandblasted with 50 µm Al2O3 veneered by IPS E-max Ceram porcelain, group C: sandblasted with 50 µm Al2O3, etching with hydrofluoric acid and veneered with P60 composite, group E: sandblasted with 50 µm Al2O3, etching with hydrofluoric acid and veneered with Tetric N-Ceram composite). All crowns were subjected to fracture strength test in the testing machine, with load application by steel ball indenter and 0.5 mm/min. cross head speed. Results: statistical analysis was carried out utilizing one-way ANOVA, LSD. The results of fracture strength value test showed the highest mean value was registered for group (A), and the lowest mean for group (E). One-way ANOVA test represented that, there was a statistically high significant different among all groups. LSD results showed a high significant difference increase in fracture resistance for Group A at p value (*P<0.001 High significant). Conclusions: Within the limitation of this study, sandblasting zirconia core with 50 µm Al2O3 and veneering with conventional ceramic produced restoration with acceptable fracture resistance value. Keywords Composite resin; Fracture resistance; Hydrofluoric acid; IPS Emax ceram; zirconium oxide.